Molecular length adjustment for organic azo-based nonvolatile ternary memory devices - Miao, Shifeng (2013)
Two conjugated small molecules with different molecular length, DPAPIT and DPAPPD, in which an electron donor dimethylamino moiety and an electron acceptor phthalimide core unit are bridged by another electron-accepting azobenzene block, were designed and synthesized. DPAPIT molecule with longer conjugation length stacked regularly in the solid state and formed uniform nanocrystalline film. The fabricated memory devices with DPAPIT as active material exhibited outstanding nonvolatile ternary memory effect with the current ratio of 1:101.7:104 for “0”, “1” and “2” states and all the switching threshold voltages lower than −3 V. In contrast, the shorter molecule DPAPPD showed amorphous microstructure and no obvious conductive switching behavior was observed in the device. The crystallinity and surface roughness of DPAPIT thin films were significantly improved as the annealing temperature increased, lowering the switching threshold voltages which are highly desirable for low-power consumption data-storage devices. It is worth noting that the tristable memory signals of DPAPIT film could also be achieved by using conductive atomic force microscopy with platinum-coated probe, which enables fabrication of nano-scale or even molecular-scale device, a significant progress for the ultra-high density data storage application. Mechanism analysis demonstrated that two charge traps with different depth in the molecular backbone were injected by charge carriers progressively as the external bias increased, resulting in the formation of three distinct conductive states (OFF, ON1 and ON2 states).